On the self-assembly of TiOx into 1D NP network nanostructures. (15th January 2015) - Redel, Engelbert; Chakravadhanula, Venkata Sai Kiran; Lan, Yanhua; Natzeck, Carsten; Heissler, Stefan
Abstract: Here, we report for the first time a 'ligand free' method of designing 1D TiOx supramolecular network materials, which starts from Ti bare metal powder. Each TiOx oxidation step has been carefully investigated with different analytical techniques, including high resolution transmission electron microscopy/high resolution scanning electron microscopy (HRTEM/HRSEM), x-ray photoelectron spectroscopy (XPS), Raman spectroscopy and superconducting quantum interference device (SQUID) measurements. The self-assembly of TiOx nanoparticles (NPs) into 1D supramolecular nanoparticle networks is induced by the formation of mixed valent Ti II, III species. The synthesis starts with etching a bare Ti surface, followed by a continuous oxidation of TiOx clusters and NPs, and it finally ends with the self-assembly into rigid 1D NPs chains. Today, such self-assembled 1D NP TiOx network materials are bridging the gap between the nanoscale and the macroscopic material world and will further provide interesting research opportunities.